The penalty kick accuracy in soccer: A new biomechanical approach - Attaallah, M.; Bassiouni, S.; Hassan, A.; Sunderland, C.; Soliman, W.; Amin, M.; Tschan, H. (Journal of Human Sport & Exercise, 2021)
The purpose of this study was to present a practical novel method to calculate the penalty kick accuracy in football. The mathematical advantage considered the ratio of the rectangle goal dimension (1:3) and equalized between horizontal axis as it longer 3 times than the vertical axis. Twelve male soccer players 16 (3) years)), height 174.7 (4.5) cm)), body mass 67.6 (5.5) kg)) volunteered to participate in this study. The players were asked to do penalty kicks where the ball is aimed at the farthest point from the centre of the target portion for shooting. The soccer goal was split into quarters at three different velocities (low, medium, and high) the calculation was conducted two times by height to width ratio (HWR) and the most common method radial error. Kinovea Software 0.8.27. were used for digitizing. The ICC demonstrated high reliability (r = .99) for digitization at the moment the ball crossed the goal line for the inter and intra-ratter reliability. There was a significant relationship between some kinematics variables of the ball and the accuracy outcome of the HWR method in the four sections of the goal (p < .05).